Partial nitrification/ANAMMOX (PN/A) membrane aerated biofilm reactor (MABR) under a low C/N ratio and metagenomics identification. Issue 1 (5th December 2022) - Li, Ming; Li, Yi; Sun, Zhiye; Liu, Jun; Li, Ting; Lan, Meichao; Zhang, Peng; Li, Baoan
Abstract : Coupled with different wastewater treatment processes, MABR wastewater treatment technology can be suitable for different wastewater and enhance their respective advantages. Abstract : The PN/A MABR has attracted much attention as a promising low-cost nitrogen removal technology with a lower carbon footprint. This study explored the minimum C/N ratio of the PN/A MABR. It was found that low lumen pressure (2–5 kPa) was beneficial for a MABR to achieve a partial nitrification process. Also, the ANAMMOX process can be coupled with partial nitrification in the MABR under low C/N conditions (<1.5). The total nitrogen removal efficiency (TNRE) can be seriously affected by DO under a low C/N ratio, even with minor fluctuations. When the C/N ratio was 3–4, the PN/A MABR can achieve a higher TNRE and the effluent water quality was more stable. The pH difference (ΔpH) between the influent and the effluent can reflect the influence of C/N and dissolved oxygen (DO) on the PN/A process. ΔpH was negatively correlated with the C/N ratio and positively correlated with DO. This study also found that Nitrosomonas, Nitrospira, Denitratisoma, Thauera, Candidatus Kuenenia, and Candidatus Brocadia played important roles in the synergy of nitrogen removal in the PN/A MABR by microbial population structure analysis using 16S rRNA and metagenomic sequencing identification techniques. The research results laid an application foundation for low C/N ratio sewage nitrogen removal and provided a technical reference for wastewater treatment plants (WWTPs) that treat municipal wastewater with a PN/A MABR.